2019
DOI: 10.3390/e21040396
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Corrosion Resistance of NbTiAlSiZrNx High-Entropy Films Prepared by RF Magnetron Sputtering

Abstract: In this study, we designed and fabricated NbTiAlSiZrNx high-entropy alloy (HEA) films. The parameters of the radio frequency (RF) pulse magnetron sputtering process were fixed to maintain the N2 flux ratio at 0%, 10%, 20%, 30%, 40%, and 50%. Subsequently, NbTiAlSiZrNx HEA films were deposited on the 304 stainless steel (SS) substrate. With an increasing N2 flow rate, the film deposited at a RN of 50% had the highest hardness (12.4 GPa), the highest modulus (169 GPa), a small roughness, and a beautiful color. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“… Liang et al (2011) found that in the nitrogen flow rate of 4 SCCM, the hardness and elastic modulus of (TiVCrZrHf)N coatings reach respectively to their maximum values of about 23.8 ± 0.8 and 267.3 ± 4.0 GPa. Furthermore, the corrosion resistance of the NbTiAlSiZrNx HEA coating was prepared by Xing et al (2019) under the various nitrogen flow rates is significantly different from that of 304 stainless steel. Lukáè et al (2020) prepared the HfNbTaTiZr HEA film that presents a nano-cell structure with fine surface microstructure and uneven distribution of defects by DC magnetron sputtering.…”
Section: Fabrication Methods Of Titanium Based Heasmentioning
confidence: 99%
“… Liang et al (2011) found that in the nitrogen flow rate of 4 SCCM, the hardness and elastic modulus of (TiVCrZrHf)N coatings reach respectively to their maximum values of about 23.8 ± 0.8 and 267.3 ± 4.0 GPa. Furthermore, the corrosion resistance of the NbTiAlSiZrNx HEA coating was prepared by Xing et al (2019) under the various nitrogen flow rates is significantly different from that of 304 stainless steel. Lukáè et al (2020) prepared the HfNbTaTiZr HEA film that presents a nano-cell structure with fine surface microstructure and uneven distribution of defects by DC magnetron sputtering.…”
Section: Fabrication Methods Of Titanium Based Heasmentioning
confidence: 99%
“…Al 0.5 CoCrCuFeNi alloy coating the surface of AZ91D by laser cladding successfully improved the corrosion resistance in 3.5 wt.% sodium chloride solution [10]. NbTiAlSiZrN x alloy thin films sputtered on 304 stainless steel exhibited good corrosion resistance in 1 N H 2 SO 4 solution [11]. Coatings of AlCr x NiCu 0.5 Mo (x = 0, 0.5, 1.0, 1.5, 2.0) alloys significantly improved the corrosion resistance of Q235 steel in 3.5% NaCl solution and a salt spray corrosion environment [12].…”
Section: Introductionmentioning
confidence: 94%
“…However, this rule cannot be generalized. Some HEFs remain amorphous, even after increasing the nitrogen content, such as in the case of NbTiAlSiZr [79], AlCoCrNi [27], FeCoNiCuVZrAl [68] and AlBCrSiTi [84] nitrides films. Liu et al explain that the amorphization tendency could result from the low enthalpy of the mixed elements, the difference between the depositing temperatures and also from a large solid/liquid interface energy [68].…”
Section: Structurementioning
confidence: 99%